1985
DOI: 10.1007/bf00411256
|View full text |Cite
|
Sign up to set email alerts
|

p-Cresol formation by cell-free extracts of Clostridium difficile

Abstract: Cell-free extracts of Clostridium difficile were shown to form p-cresol by decarboxylation of p-hydroxyphenylacetic acid. This activity required both high and low molecular weight fractions. The active component of the low molecular weight fraction had properties of an amino acid and could be replaced by serine, threonine or the corresponding alpha keto acids. Pyruvate was shown to function catalytically. Since the high molecular weight fraction was O2-sensitive and since dithionite was as effective as pyruvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 4 publications
1
36
0
Order By: Relevance
“…Sulfate depletion arises in the gut, both because of impaired transport of free sulfate in the bloodstream and impaired sulfate synthesis by eNOS [63,64]. Disruption of gut bacteria, exposure to toxic phenolic compounds necessary to enable sulfate transport, and deficient sulfate supply to the mucopolysaccharides in the gut all contribute to the leaky gut syndrome that is a common feature in autism [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfate depletion arises in the gut, both because of impaired transport of free sulfate in the bloodstream and impaired sulfate synthesis by eNOS [63,64]. Disruption of gut bacteria, exposure to toxic phenolic compounds necessary to enable sulfate transport, and deficient sulfate supply to the mucopolysaccharides in the gut all contribute to the leaky gut syndrome that is a common feature in autism [51].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this unique phenotype is also associated with excess synthesis of p-cresol, via a pathway involved in tyrosine breakdown. These authors go on to propose that the known sulfate deficiency associated with autism [61,62] may be explained by the depletion of sulfate through sulfation of p-cresol produced from tyrosine by Clostridium difficile in the gut [63,64], in order to detoxify it. As we will explain in the next section, we believe that, in fact, p-cresol and other phenolic compounds are part of the solution rather than the cause, with respect to impaired sulfate transport.…”
Section: Gut Dysbiosis Autism and Colitismentioning
confidence: 99%
See 1 more Smart Citation
“…It requires para hydroxyl substitution for oxidation of the aromatic alkyl group. Of those substrates tested, pCr elicits the greatest specific activity to PCMH, suggesting that pCr, a naturally occurring cresol (6,11,18) is the natural substrate for the enzyme. Results indicated that the PC-07 PCMH is not dependent on pyridine or flavin cofactors and therefore requires another, as yet unidentified, electron carrier protein. A likely candidate is azurin, a small copper-containing protein (1) determined to be the natural electron acceptor in aerobic Pseudomonas strains displaying PCMH activity (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970's Clostridium difficile and Clostridium scatologenes were shown to produce p -cresol with p -hydroxyphenylacetate as the immediate precursor [Elsden et al, 1976]. Subsequently, pcresol formation by decarboxylation of p -hydroxyphenylacetate was reported for Lactobacillus strains [Yokoyama and Carlson, 1981] and for cell-free extracts of C. difficile [D'Ari and Barker, 1985].…”
Section: Occurrence and Biological Function Of The 4hpad Systemmentioning
confidence: 99%